If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -4 = 3(5x + -4) Combine like terms: 15 + -4 = 11 11 = 3(5x + -4) Reorder the terms: 11 = 3(-4 + 5x) 11 = (-4 * 3 + 5x * 3) 11 = (-12 + 15x) Solving 11 = -12 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 11 + -15x = -12 + 15x + -15x Combine like terms: 15x + -15x = 0 11 + -15x = -12 + 0 11 + -15x = -12 Add '-11' to each side of the equation. 11 + -11 + -15x = -12 + -11 Combine like terms: 11 + -11 = 0 0 + -15x = -12 + -11 -15x = -12 + -11 Combine like terms: -12 + -11 = -23 -15x = -23 Divide each side by '-15'. x = 1.533333333 Simplifying x = 1.533333333
| 18x+4y=162000 | | V=c-crt | | 15x+3=18x | | 3(2t+10)= | | 4*6+(6x)=150 | | log^4(9-4x)=1 | | -8x-(-3x+6)=4-x | | x+(1.10-x)=1.10 | | -44-7k=12-k | | C-11=19 | | X+2y=87.4 | | 5u-14=26 | | 0.5p+0.9p+2= | | -2y+3=y-12 | | 108X^5+.04=0 | | 68=4v+16 | | 24x=86 | | (8-z)*(5z+3)=0 | | e=0.5x-1 | | (8-z)*(5z-3)=0 | | 4=5y-3y-2 | | 9y-36=-10y+7 | | -16f+1=-17f+16 | | c-0.25c=25 | | -8d=11d+19 | | 4z^2=x^2+y^2 | | 1.35=1.85(b+-13)+14.3 | | -0.4=1.6(w+2)-0.4 | | -0.99(h-7)=-7.92 | | Xsquared+ysquared=153 | | -3(d-8.8)=6.3 | | 31(m-963)+63=931 |